Prospective Mathematics Teachers’van Hiele’s Geometry Thinking and Habits of Mind: A Description of Hard Skill and Soft Skill by Gender - Nopriana, Tri; Herman, Tatang; Martadiputra, Bambang Avip Priatna (EDUPEDIA Publisher, 2023)
Geometric thinking level and habits of mind were important hard and soft skills required of prospective mathematics teachers. The purpose of this study is to describe the van Hiele geometric thinking level and habits of mind of prospective mathematics teachers. The descriptive quantitative research method was used. There were 31 female and 17 male prospective mathematics teachers in the sample. The research instrument for measuring geometric level was derived from Usikin's (1982) van Hiele geometric thinking test and a habits of mind questionnaire. According to the findings of this study, prospective mathematics teachers' ability to think geometrically has progressed to the stage of analysis and informal deduction. Furthermore, male prospective mathematics teachers achieved the highest level of geometric thinking, known as rigor. Furthermore, both as a whole and in terms of indicators, prospective mathematics teachers' habits of mind fall into the strong category. Male prospective mathematics teachers have more positive habits of mind than female prospective mathematics teachers. The study's findings can help lecturers, particularly those in the mathematics education study program, determine students' hard and soft skills at the end of the year. Prospective mathematics teachers can also be assigned by institutions based on their geometric thinking and habits of mind.